Adoption of agroforestry for sustainability in agriculture - Gill, A S (Indian Farming, 2015)
The Indian farming community is passing through a hard time. There may be several reasons. The primary reason seems to be the fast changing agro-climatic conditions which has resulted in low rainfall pattern and high temperatures. Many states are even facing drinking water problems. The basic reasons are less tree cover, less forest cover and deforestation process. Basic problems can be solved with the adoption of agroforestry systems. Tree-crop interface has an added advantage because in their association there is no competition among them for plant nutrients and soil moisture as both derive these from different zones. Trees have a deep-rooted system whereas, crops have a shallow root system. Further, giving greater preference to nitrogen fixing trees (NFT’s), in addition extending various benefits to its associated components, it improves the soil health. Various agroforestry systems extend insurance cover to the farming community, which is an added advantage.